2014
DOI: 10.1016/j.thromres.2013.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of chest radiography in predicting pulmonary hypertension: A case-control study

Abstract: a b s t r a c t a r t i c l e i n f oObjective: To assess the accuracy of chest radiography (CXR) in predicting pulmonary hypertension (PH). Methods: We studied 108 consecutive patients with suspected PH who underwent right heart catheterization (RHC). All were PH treatment naives. Hemodynamic criteria included a mean pulmonary artery pressure N 25 mmHg at rest, and a mean pulmonary wedge pressure b 15 mmHg. Postero-anterior and lateral CXR were obtained shortly before RHC. To avoid a selection bias which coul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“… 14 , 15 Dilatation of the pulmonary artery trunk and of the RV with pruning of peripheral pulmonary vessels were regarded as suggestive of chronic thromboembolic pulmonary hypertension (CTEPH). 16 …”
Section: Methodsmentioning
confidence: 99%
“… 14 , 15 Dilatation of the pulmonary artery trunk and of the RV with pruning of peripheral pulmonary vessels were regarded as suggestive of chronic thromboembolic pulmonary hypertension (CTEPH). 16 …”
Section: Methodsmentioning
confidence: 99%
“…Signs of PH on CXR include isolated enlargement of the RV, right descending pulmonary artery diameter >16 mm, and pruning of the pulmonary vessels. Miniati et al [76] studied the accuracy of these findings in predicting PH and found their weighted sensitivity to be 96.9% and weighted specificity to be 99.8%. Computed tomography (CT) of the chest has also been used to evaluate the severity of PH.…”
Section: Diagnosismentioning
confidence: 99%
“…[16] CXR has a high sensitivity (96.9%) and specificity (99.1%) for detection of PAH when pre-test probability is 50% or more. [17] Miniati et al [17] suggested that CXR findings that are suggestive of PAH are sufficient to warrant further investigation by RHC and that a normal CXR does not exclude the presence of PH. The severity of PH, however, cannot be correlated with CXR changes.…”
Section: Discussionmentioning
confidence: 99%